A scoping review of non-pharmacological perinatal interventions impacting maternal sleep and maternal mental health - Ladyman C; Sweeney B; Sharkey K; Bei B; Wright T; Mooney H; Huthwaite M; Cunningham C; Firestone R; Signal TL (BioMed Central Ltd, 2022)
BACKGROUND: A woman's vulnerability to sleep disruption and mood disturbance is heightened during the perinatal period and there is a strong bidirectional relationship between them. Both sleep disruption and mood disturbance can result in significant adverse outcomes for women and their infant. Thus, supporting and improving sleep in the perinatal period is not only an important outcome in and of itself, but also a pathway through which future mental health outcomes may be altered. METHODS: Using scoping review methodology, we investigated the nature, extent and characteristics of intervention studies conducted during the perinatal period (pregnancy to one-year post-birth) that reported on both maternal sleep and maternal mental health. Numerical and descriptive results are presented on the types of studies, settings, sample characteristics, intervention design (including timeframes, facilitation and delivery), sleep and mood measures and findings. RESULTS: Thirty-seven perinatal interventions were identified and further described according to their primary focus (psychological (n = 9), educational (n = 15), lifestyle (n = 10), chronotherapeutic (n = 3)). Most studies were conducted in developed Western countries and published in the last 9 years. The majority of study samples were women with existing sleep or mental health problems, and participants were predominantly well-educated, not socio-economically disadvantaged, in stable relationships, primiparous and of White race/ethnicity. Interventions were generally delivered across a relatively short period of time, in either the second trimester of pregnancy or the early postnatal period and used the Pittsburgh Sleep Quality Index (PSQI) to measure sleep and the Edinburgh Postnatal Depression Scale (EPDS) to measure mood. Retention rates were high (mean 89%) and where reported, interventions were well accepted by women. Cognitive Behavioural Therapies (CBT) and educational interventions were largely delivered by trained personnel in person, whereas other interventions were often self-delivered after initial explanation. CONCLUSIONS: Future perinatal interventions should consider spanning the perinatal period and using a stepped-care model. Women may be better supported by providing access to a range of information, services and treatment specific to their needs and maternal stage. The development of these interventions must involve and consider the needs of women experiencing disadvantage who are predominantly affected by poor sleep health and poor mental health.
© The Author(s) 2022
Keywords: Health inequities; Intervention; Mental health; Mood; Perinatal; Postnatal; Postpartum; Pregnancy; Sleep; Female; Humans; Infant; Male; Maternal Health; Mental Health; Pregnancy; Psychiatric Status Rating Scales; Sleep; Sleep Initiation and Maintenance Disorders; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services